2016
DOI: 10.1021/acs.nanolett.5b04981
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Cesium Lead Halide Perovskite Nanocrystals in a Droplet-Based Microfluidic Platform: Fast Parametric Space Mapping

Abstract: Prior to this work, fully inorganic nanocrystals of cesium lead halide perovskite (CsPbX3, X = Br, I, Cl and Cl/Br and Br/I mixed halide systems), exhibiting bright and tunable photoluminescence, have been synthesized using conventional batch (flask-based) reactions. Unfortunately, our understanding of the parameters governing the formation of these nanocrystals is still very limited due to extremely fast reaction kinetics and multiple variables involved in ion-metathesis-based synthesis of such multinary hali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
442
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 444 publications
(453 citation statements)
references
References 81 publications
7
442
0
4
Order By: Relevance
“…Later on, by means of a droplet-based microfluidic platform, allowing for online absorption/PL measurements, the same group explored the formation mechanism of these perovskite NCs. 61 Koolyk et al 62 investigated the growth process of caesium lead halide perovskite NCs by time-dependent TEM characterization. They found that the growth kinetics are different for CsPbBr 3 and CsPbI 3 , providing a model for each growth process.…”
Section: Synthesis Of Perovskite Ncsmentioning
confidence: 99%
“…Later on, by means of a droplet-based microfluidic platform, allowing for online absorption/PL measurements, the same group explored the formation mechanism of these perovskite NCs. 61 Koolyk et al 62 investigated the growth process of caesium lead halide perovskite NCs by time-dependent TEM characterization. They found that the growth kinetics are different for CsPbBr 3 and CsPbI 3 , providing a model for each growth process.…”
Section: Synthesis Of Perovskite Ncsmentioning
confidence: 99%
“…For instance, all-inorganic CsPbX 3 nanocrystals are found to have much higher stability than organic metal halide perovskites MAPbX 3 , and exhibit narrow emissions with high PLQEs [69,70], which made them highly attractive for lasing and LEDs [34]. Tuning the photoluminescence of cesium lead halide perovskites could be realized by both compositional control and quantum size engineering [71,72]. It was demonstrated that by changing the capping organic ligand, the morphology of CsPbX 3 could be effectively tuned from nanocubes to nanowires and nanoplatelets with different sizes (Figure 4) [73][74][75].…”
Section: Morphological Low Dimensional Metal Halide Perovskitesmentioning
confidence: 99%
“…To date, all-inorganic cesium lead halide perovskite have generated considerable attention because of their higher stability and outstanding optoelectronic properties comparable to the hybrid organic-inorganic perovskites [17][18][19][20]. Thus, a large number of CsPbX 3 (X = I, Br, Cl) perovskite nanostructures such as nanocrystals [21], nanowires [22], microsheets [23,24], nanocubes, were prepared by solution processing approach. Furthermore, the physical properties of all-inorganic nanocrystals could be adjusted by their geometric shape and size [25].…”
Section: Introductionmentioning
confidence: 99%